Exploring nonvoting and electoral integrity in the 2016 presidential election. Issue 4 (1st October 2020) - Clark, Nicholas; Peterson, Rolfe
ABSTRACT: While voter turnout has been a subject of research for decades, comparatively little attention has been paid to nonvoters. Just as voters can be mobilized by demographic and contextual factors, we theorize that these factors can serve to demobilize people as well. Our study identifies four potential types of nonvoters and theorizes how they differ in their demographics and their motivations for not voting. Using data from the Cooperative Congressional Election Study (CCES) and the Electoral Integrity Project (EIP), we examine nonvoters in the 2016 general election in the United States. We find that apathetic, obstructed, incapable, and conditional nonvoters are each unique. Low electoral integrity can demobilize obstructed nonvoters, while apathetic, incapable, and conditional nonvoters are driven more by political and demographic factors.